Anti-Flutter Adhesive Composition
Patent Information
- Application Number
- JP2023526614
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-05
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-11-05
Smart Images

Figure 0007639131000001 
Figure 0007639131000002 
Figure 0007639131000003
Abstract
Description
[Technical field]
[0001] [Technical field] The present invention relates to an anti-flutter adhesive composition comprising: a) at least one ethylenically unsaturated rubber; b) at least one PVC homopolymer having a K value of 67-75; c) at least one PVC copolymer having a K value of 60-75; d) at least one epoxy resin; e) at least one epoxy curing agent; f) at least one first organic peroxide having a decomposition temperature of 125-180° C.; and g) at least one second organic peroxide having a decomposition temperature below 125° C. The anti-flutter adhesive composition can be cured over a wide temperature range and has excellent shear strength and good appearance after curing. [Background technology]
[0002] [Background of the invention] Anti-flutter adhesives are mainly used for bonding the inner and outer panels of automotive parts, reducing the mutual vibration between the outer and inner panels. Generally, anti-flutter adhesives are heated in a baking window of 170-200°C according to the automotive production line, so that the anti-flutter adhesive can be properly cured. However, the current baking window requires high energy input and does not meet the global trend of energy saving. Summary of the Invention [Problem to be solved by the invention]
[0003] Therefore, there is a need to develop an anti-flutter adhesive that can be cured at a lower temperature in the range of 150-170°C to save energy, and more preferably, over a wide temperature range spanning 150-200°C so that it can be applied to different automobile production lines. [Means for solving the problem]
[0004] [Summary of the invention] The present invention relates to the following: a) at least one ethylenically unsaturated rubber; b) at least one PVC homopolymer having a K value of 67 to 75; c) at least one PVC copolymer having a K value of 60 to 75; d) at least one epoxy resin; e) at least one epoxy hardener; f) at least one first organic peroxide having a decomposition temperature of 125 to 180° C.; and g) at least one second organic peroxide having a decomposition temperature of less than 125° C.; An anti-flutter adhesive composition comprising: Where: The amount of the first organic peroxide is 0.4 to 0.8 wt. % based on the total weight of the composition; and The amount of the second organic peroxide is 0.2 to 1 wt % based on the total weight of the composition.
[0005] The anti-flutter adhesive composition can be cured at a temperature in the range of 150 to 200°C.
[0006] The present invention also relates to a cured product of the anti-flutter adhesive composition. The cured anti-flutter adhesive composition has excellent shear strength on a variety of substrates and exhibits a good appearance.
[0007] The present invention also relates to articles bonded or filled with the cured anti-flutter adhesive composition.
[0008] [Detailed Description of the Invention] In the following sections, the invention will be described in more detail. Each aspect so described may be combined with any other aspect or aspects, unless expressly indicated to the contrary. In particular, any feature indicated as being preferred or advantageous may be combined with any other feature or features indicated as being preferred or advantageous. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] In the context of the present invention, the terms used are to be construed in accordance with the following definitions, unless the context dictates otherwise.
[0010] As used herein, the singular forms "a," "an," and "the" include both singular and plural referents unless the context clearly dictates otherwise.
[0011] As used herein, the terms "comprising," "comprises," and "comprised of" are synonymous with "including," "includes," or "containing," and are inclusive or open-ended and do not exclude additional, unrecited components, elements, or process steps.
[0012] The recitation of numerical endpoints includes all values and fractions subsumed within the respective ranges, as well as the recited endpoints.
[0013] All references cited herein are incorporated by reference in their entirety.
[0014] Unless otherwise defined, all terms used in disclosing the present invention, including technical and scientific terms, have the meanings commonly understood by one of ordinary skill in the art to which the present invention belongs. By way of further guidance, definitions of terms are included to better understand the teachings of the present invention.
[0015] In the context of this disclosure, a number of terms are used.
[0016] The term "ethylenically unsaturated" indicates at least one site of unsaturation that is not aromatic.
[0017] The term "rubber" refers to a polymer that has the ability to return to its original shape after being stretched or deformed.
[0018] The term "K value" denotes the degree of polymerization of a polymer. It is determined in accordance with DIN EN ISO 1628-2.
[0019] The term "decomposition temperature" refers to the temperature at which 50% of the peroxide substantially dissociates / decomposes into free radicals within one hour and is capable of initiating other reactions. This is determined by thermogravimetric analysis (TGA). Preferably, a TA instrument Q500 is used for the analysis, which is performed under nitrogen at a heating rate of 5°C / min.
[0020] Ethylenically unsaturated rubber The anti-flutter adhesive composition of the present invention comprises at least one ethylenically unsaturated rubber.Suitable ethylenically unsaturated rubbers include natural rubber, synthetic rubber, and mixtures thereof.In some embodiments, the ethylenically unsaturated rubber preferably has a number average molecular weight of 30,000 g / mol or more, such as 50,000 g / mol, 100,000 g / mol, and 300,000 g / mol, as measured by GPC.
[0021] Representative examples of suitable synthetic rubbers include, but are not limited to, styrene-butadiene rubber (SBR), styrene-butadiene-vinylpyridine rubber, chloroprene rubber, isoprene rubber (IR), isoprene-isobutylene rubber (IIR), polybutadiene rubber (BR), ethylene-propylene-diene monomer terpolymer (EPDM), acrylonitrile-butadiene rubber (NBR), polysiloxanes containing ethylenic unsaturation, polyurethanes containing ethylenic unsaturation, and mixtures thereof.
[0022] In some embodiments, the ethylenically unsaturated rubber is preferably a styrene-butadiene rubber (SBR), a polybutadiene rubber (BR), or a mixture thereof.
[0023] Examples of commercially available ethylenically unsaturated rubbers include, for example, SBR 1009 (manufactured by Lion Elastomer Co., Ltd.); BR 9000 (manufactured by Beijing Yanshan Petrochemical Rubber Chemical Co., Ltd.); BR 9000 (manufactured by Sinopec Gaoqiao Petrochemical Co., Ltd.).
[0024] In some embodiments of the present invention, the amount of ethylenically unsaturated rubber is 2-10% by weight, preferably 4-8% by weight, based on the total weight of the anti-flutter adhesive composition.
[0025] <PVC polymer> The anti-flutter adhesive composition of the present invention comprises at least one PVC homopolymer having a K value of 67-75 and at least one PVC copolymer having a K value of 60-75.
[0026] PVC copolymers can result from the copolymerization of vinyl chloride with one or more ethylenically unsaturated comonomers.Comonomers useful for forming PVC copolymers include, but are not limited to, vinylidene halides, such as vinylidene chloride or vinylidene fluoride, vinyl carboxylates, such as vinyl acetate, vinyl propionate or vinyl butyrate, vinyl aromatic derivatives, such as styrene or vinyl naphthalene, olefins, such as ethylene, propene or 1-butene.
[0027] In some embodiments of the present invention, the PVC homopolymer preferably has a K value of 68-71.
[0028] In some embodiments of the present invention, the PVC copolymer preferably has a K value of 63-70.
[0029] Surprisingly, it has been found that when both PVC homopolymers and PVC copolymers having suitable K values are incorporated into the composition, the anti-flutter adhesive composition can be cured over a wide range of temperatures and the cured product has good appearance and excellent shear strength against a variety of substrates, such as aluminum panels, cold rolled steel, and galvanized steel.
[0030] Examples of commercially available PVC homopolymers are, for example, VESTOLIT E 7031 and P 1353 K (VESTOLIT GmbH & Co. KG). Examples of commercially available PVC copolymers are, for example, PCMA 12 (Shenyang Chemical); and Lacovyl PA 1384 (Arkema).
[0031] In some embodiments of the present invention, the amount of PVC homopolymer is preferably 6-15 wt.%, more preferably 7-10 wt.%, and even more preferably 8-9 wt.%, based on the total weight of the anti-flutter adhesive composition.
[0032] In some embodiments of the present invention, the amount of PVC copolymer is preferably 2-5 wt %, more preferably 3-4 wt %, based on the total weight of the anti-flutter adhesive composition.
[0033] <Epoxy resin> The anti-flutter adhesive composition of the present invention includes at least one epoxy resin. The epoxy resin may be any common epoxy resin containing at least one epoxy group per molecule, and preferably contains multiple epoxy groups per molecule. Examples of epoxy resins include, but are not limited to, bisphenol A epoxy resin, bisphenol F epoxy resin, biphenyl epoxy resin, naphthalene epoxy resin, diphenyl ether epoxy resin, diphenyl thioether epoxy resin, hydroquinone epoxy resin, biphenyl novolac epoxy resin, cresol novolac epoxy resin, phenol novolac epoxy resin, bisphenol A novolac epoxy resin, trisphenol epoxy resin, tetraphenylol ethane epoxy resin, and any combination thereof.
[0034] Examples of commercially available epoxy resins are, for example, DER331 (Olin); EPON828 (Shell Chemical); YD-128 (Kukdo Chemical); and EPICLON N-665 (Dainippon Ink and Chemicals).
[0035] In some embodiments of the present invention, the amount of epoxy resin is preferably 1-6 wt %, more preferably 3-5 wt %, based on the total weight of the anti-flutter adhesive composition.
[0036] <Epoxy hardener> The anti-flutter adhesive composition of the present invention comprises at least one epoxy curing agent. The epoxy curing agent refers to any curing agent commonly used for epoxy systems, including, but not limited to, polyamides, amines, imidazoles, and their derivatives. Exemplary curing agents include dicyandiamide, polyamide resins based on dimerized fatty acids and polyamines, methyldiethanolamine, triethanolamine, diethylaminopropylamine, benzyldimethylamine, m-xylylenedi(dimethylamine), benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1-methylimidazole, 2-methylimidazole, and 2,4-diethylimidazole.
[0037] Examples of commercially available epoxy hardeners include, for example, Versamid 140 (Gabriel Performance Products); Ancamine TEPA (Evonik); Ajicure PN-H (Ajinomoto Fine-Techno Co.); Fujicure-FXR-1090FA (T&K Toka); 1,2-dimethyl imidazole (Shikoku Kasei Co.); 2E4MI (Evonik); Gaskamine 240 (Mitsubishi Gas Chemical Co.); and Ecure 14 (Alz Chem).
[0038] In some embodiments of the present invention, the amount of epoxy curing agent is preferably 0.01 to 2 wt %, more preferably 0.4 to 0.8 wt %, based on the total weight of the anti-flutter adhesive composition.
[0039] ≪Organic peroxide≫ The anti-flutter adhesive composition of the present invention comprises at least one first organic peroxide having a decomposition temperature of 125-180°C and at least one second organic peroxide having a decomposition temperature less than 125°C.
[0040] In some embodiments of the present invention, the first organic peroxide preferably has a decomposition temperature of 130 to 160°C, more preferably 130 to 140°C.
[0041] In some embodiments of the present invention, the first organic peroxide is preferably dicumyl peroxide.
[0042] In some embodiments of the present invention, the second organic peroxide preferably has a decomposition temperature of 50 to 120°C, more preferably 80 to 120°C, and even more preferably 100 to 115°C.
[0043] In some embodiments of the present invention, the second organic peroxide is preferably 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane.
[0044] Examples of first organic peroxides include, but are not limited to, dicumyl peroxide (DCP), di(tertbutyl) peroxide, and 2,5-dimethyl-2,5-bis(t-butylperoxy)-hexine (DBPH).
[0045] Examples of second organic peroxides include, but are not limited to, bis(2,4-dichlorobenzoyl) peroxide (DCBP), dibenzoyl peroxide, and 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane.
[0046] Examples of commercially available first organic peroxides include DCP (manufactured by Taicang Plastic Additive Co., Ltd.); and DCP-40 (manufactured by Jiangsu Daoming Chemical Co., Ltd.).
[0047] Examples of commercially available second organic peroxides include, for example, Varox 231 XL (Vanderbilt Chemicals, LLC); and TMCH-40 (United Initiators).
[0048] In some embodiments of the present invention, the amount of the first organic peroxide is 0.4 to 0.8 wt %, preferably 0.5 to 0.7 wt %, based on the total weight of the anti-flutter adhesive composition.
[0049] In some embodiments of the present invention, the amount of the second organic peroxide is 0.2-1 wt %, preferably 0.3-0.4 wt %, based on the total weight of the anti-flutter adhesive composition.
[0050] Surprisingly, it has been found that when two organic peroxides having suitable decomposition temperatures are incorporated into the composition, the anti-flutter adhesive composition can be cured over a wide range of temperatures and has good appearance and excellent shear strength against a variety of substrates, such as aluminum panels, cold rolled steel, galvanized steel, etc.
[0051] Moreover, it has been surprisingly found that a PVC homopolymer and a PVC copolymer having suitable K values and two organic peroxides having suitable decomposition temperatures act synergistically to achieve cure of the anti-flutter adhesive composition over a wide range of temperatures.
[0052] Optional Additives The anti-flutter adhesive composition may further comprise optional additives. The selection of suitable additives for the anti-flutter adhesive composition of the present invention can be determined in each case by those skilled in the art depending on the specific application of the anti-flutter adhesive composition.
[0053] <Nano-sized inorganic filler> The anti-flutter adhesive composition of the present invention may optionally contain at least one nano-sized inorganic filler. The nano-sized inorganic filler of the present invention preferably has a 70% volume particle size (D70) of 20 to 80 nm, more preferably a D70 of 40 to 60 nm, and even more preferably a D70 of 50 to 55 nm. The D70 value indicates the cumulative volume distribution curve in which 70% by volume of the particles have a diameter less than said value. The particle size of the nano-sized inorganic filler is preferably measured according to the laser diffraction method using a Partica LA-950 Laser Scattering Particle Size Distribution Analyzer (manufactured by Horiba).
[0054] An example of a commercially available nano-sized inorganic filler is, for example, TA 17 (manufactured by Wuhu Perfection Nanometer New Material Co., Ltd.).
[0055] In some embodiments of the present invention, the amount of the nano-sized inorganic filler is preferably 0-30 wt %, more preferably 10-30 wt %, and even more preferably 15-20 wt %, based on the total weight of the anti-flutter adhesive composition.
[0056] <Fumed silica> The anti-flutter adhesive composition of the present invention is 150 to 250 m 2 / g, preferably 170 to 230 m 2 The composition may optionally contain at least one fumed silica having a BET surface area of 1000 nm / g, the BET surface area value being determined according to GB / T 10722.
[0057] An example of a commercially available fumed silica is, for example, CAB-O-SIL M-5 (Cabot Corporation).
[0058] In some embodiments of the present invention, the range is 150 to 250 m. 2The amount of fumed silica having a BET surface area of 1000 nm / g is preferably 0 to 3 wt. %, more preferably 1.5 to 3 wt. %, and even more preferably 2 to 3 wt. %, based on the total weight of the anti-flutter adhesive composition.
[0059] Surprisingly, it has been found that the anti-sagging property of anti-flutter adhesive compositions is greatly improved when nano-sized inorganic particles and fumed silica with suitable BET surface area are incorporated into the composition.This is important for anti-flutter adhesive compositions because anti-flutter adhesive compositions are usually applied to automobile panels with large gaps.If the adhesive composition sags, the cured product of the adhesive composition may have poor appearance and anti-flutter properties.
[0060] <Plasticizer> The anti-flutter adhesive composition of the present invention may optionally include at least one plasticizer. The plasticizer of the present invention refers to any common plasticizer known in the art. Examples of plasticizers include, but are not limited to, epoxy-based plasticizers (such as epoxidized soybean oil, epoxidized linseed oil, and epoxidized cottonseed oil), phosphate esters, aliphatic esters, aromatic esters, dioctyl terephthalate (DOTP), dioctyl phthalate (DOP), di(isononyl)phthalate (DINP), di(isodecyl)phthalate (DIDP), diundecyl phthalate (DUP), dioctyl adipate (DOA), diisononyl adipate (DINA), trioctyl trimellitate (TOTM), trioctyl phosphate (TOP), tricresyl phosphate (TCP), and the like. The plasticizers may be used alone or in any combination.
[0061] Examples of commercially available plasticizers are, for example, DOTP (Sinopharm); DOA (Wengiang Chemical); DINP (Taizhou Liancheng Chemical).
[0062] In some embodiments of the present invention, the amount of plasticizer is 0-40 wt%, preferably 15-30 wt%, based on the total weight of the anti-flutter adhesive composition.
[0063] <Heat stabilizer> The anti-flutter adhesive composition of the present invention may optionally contain at least one heat stabilizer.The heat stabilizer in the present invention refers to any common heat stabilizer known in the art that functions to protect PVC polymer during heating process.Examples of heat stabilizer include, but are not limited to, methyltin mercaptide, butyltin mercaptide, and octyltin mercaptide.
[0064] In some embodiments of the present invention, the amount of heat stabilizer is 0-0.2 wt %, preferably 0.01-0.1 wt %, based on the total weight of the anti-flutter adhesive composition.
[0065] <Foaming agent> The anti-flutter adhesive composition of the present invention may optionally include at least one blowing agent known in the art. The blowing agent causes the formation of gas, which then molds pores to form a porous structure in the cured product of the anti-flutter adhesive composition. The blowing agent of the present invention may be a physical blowing agent, a chemical blowing agent, or a combination of the two. Examples of blowing agents include, but are not limited to, carbon dioxide gas, nitrogen gas, air, halogenated hydrocarbons, bicarbonates, azo compounds, and hydrazine derivatives.
[0066] In some embodiments of the present invention, the amount of the foaming agent is 0-1 wt %, preferably 0.2-0.6 wt %, based on the total weight of the anti-flutter adhesive composition.
[0067] <Crosslinking agent> The anti-flutter adhesive composition of the present invention may optionally include at least one crosslinking agent known in the art. The crosslinking agent preferably has at least two ethylenically unsaturated groups. Examples of crosslinking agents include, but are not limited to, diacrylates, such as zinc dimethacrylate and magnesium dimethacrylate; alcohols, acrylic and methacrylic acid esters, such as trimethylolpropane trimethacrylate; and vinyl acrylate.
[0068] In some embodiments of the present invention, the amount of crosslinker is 0-10 wt%, preferably 0.1-5 wt%, based on the total weight of the anti-flutter adhesive composition.
[0069] <Thermal expandable microspheres> The anti-flutter adhesive composition of the present invention may optionally include at least one thermally expandable microsphere known in the art to aid in foaming of the composition. The thermally expandable microsphere may be a microsphere formed by surrounding a material that easily becomes a gas and expands upon heating, such as isobutane, propane, or pentane, methylbutane, within an elastic shell. The elastic shell may be made of a material that melts or bursts upon thermal expansion. Examples of such materials that make up the shell include, but are not limited to, vinylidene chloride / acrylonitrile copolymer, acrylonitrile / methacrylonitrile copolymer, poly(methyl methacrylate), polyacrylonitrile, poly(vinylidene chloride), and the like.
[0070] Examples of commercially available thermoexpandable microspheres include Matsumoto Microsphere (manufactured by Matsumoto Yushi Seiyaku Co., Ltd.); Advancell EM H 204 (manufactured by Sekisui Chemical Co., Ltd.).
[0071] In some embodiments of the present invention, the amount of thermally expandable microspheres is 0-1 wt%, preferably 0.2-0.4 wt%, based on the total weight of the anti-flutter adhesive composition.
[0072] <More inorganic fillers> The anti-flutter adhesive composition of the present invention may optionally contain at least one additional inorganic filler different from the nano-sized inorganic filler, preferably having a 70% volumetric particle size (D70) greater than 500 nm. Examples of additional inorganic fillers include, but are not limited to, calcium carbonate and metal oxides, such as titanium dioxide, magnesium oxide, zinc oxide, iron oxide, chromium oxide, zirconium oxide, and aluminum oxide.
[0073] In some embodiments of the present invention, the amount of the further inorganic filler is 0-10 wt. %, preferably 2-6 wt. %, based on the total weight of the anti-flutter adhesive composition.
[0074] Other optional additives that may be used in the anti-flutter adhesive composition of the present invention include, but are not limited to, antioxidants; biocides; dyes; pigments; and mixtures thereof.
[0075] In a preferred embodiment, the anti-flutter adhesive composition comprises: 2-10% by weight of at least one ethylenically unsaturated rubber; 6-15% by weight of at least one PVC homopolymer having a K value of 67-75; 2-5% by weight of at least one PVC copolymer having a K value of 60-75; 1-6% by weight of at least one epoxy resin; 0.01-2 wt. % of at least one epoxy hardener; 0.4-0.8 wt. % of at least one first organic peroxide having a decomposition temperature of 125-180° C.; 0.2-1 wt. % of at least one second organic peroxide having a decomposition temperature below 125° C.; 0-30 wt. % of at least one nanosized inorganic filler; 0~3% by weight, 150~250m 2 at least one fumed silica having a BET surface area of 1.0 to 1.0 g / g; 0-40% by weight of at least one plasticizer; 0-0.2 wt. % of at least one heat stabilizer; 0-1 wt. % of at least one blowing agent; 0-10% by weight of at least one crosslinker; 0-10% by weight of at least one further inorganic filler; and 0-1 wt. % of at least one thermally expandable microsphere; Here, the weight percentages of all components total 100 weight %.
[0076] The anti-flutter adhesive composition of the present invention comprises at least one ethylenically unsaturated rubber, at least one PVC homopolymer having a K value of 67-75, at least one PVC copolymer having a K value of 60-75, at least one epoxy resin, at least one epoxy curing agent, at least one first organic peroxide having a decomposition temperature of 125-180°C, at least one second organic peroxide having a decomposition temperature below 125°C, and optional additives, such as at least one nano-sized inorganic filler, 150-250m 2 The composition can be prepared by intimately mixing at least one fumed silica having a BET surface area of 1000 nm / g, at least one plasticizer, at least one heat stabilizer, at least one foaming agent, at least one crosslinking agent, at least one additional inorganic filler, and at least one thermally expandable microsphere, and the like.
[0077] The anti-flutter adhesive composition of the present invention can be applied to a substrate surface via a scarper, sprayer or extruder and cured at a temperature in the range of 150-200°C.
[0078] The shear strength of the anti-flutter adhesive composition of the present invention after curing under different temperatures against various substrates including cold rolled steel, galvanized steel, and aluminum panels can be measured according to SAE J1523 by mating two substrates with the adhesive composition.
[0079] The shear strength of the anti-flutter adhesive composition of the present invention is preferably 0.2 MPa or more after curing at a temperature in the range of 150 to 200°C, and the cured adhesive is completely separated from the surface of one of the substrates after the two substrates are pulled apart.
[0080] The appearance of the cured anti-flutter adhesive composition of the present invention can be evaluated by checking the stickiness of the surface of the cured anti-flutter adhesive composition, and by checking whether it is elastic and whether there are cracks on the surface by finger pressure.
[0081] The cured anti-flutter adhesive composition of the present invention preferably has a resilient, non-tacky, and crack-free surface.
[0082] In the present invention, the anti-sagging property of the adhesive composition after curing under different temperatures can be evaluated according to GB / T 31113-2014.
[0083] The cured anti-flutter adhesive composition preferably has a displacement of 5 mm or less. EXAMPLES
[0084] [Example] The present invention will be described and illustrated in more detail with reference to the following examples. The examples are intended to help those skilled in the art to better understand and practice the present invention, but are not intended to limit the scope of the present invention. All numerical values in the examples are by weight unless otherwise specified.
[0085] <Examples 1 to 22> In the examples, the following materials were used: TIFF0007639131000001.tif245170
[0086] The components according to Table 1a and Table 1b were used to prepare an anti-flutter adhesive composition as an example (Ex.). The components were mixed under vacuum for 100 minutes at a speed of 30 rpm using a kneader (LK 11 1 manufactured by Hermann Linden Maschinenfabrik). During the preparation process, the temperature was controlled at about 35°C and the vacuum degree was controlled at about 0.7 Mpa.
[0087] The anti-flutter adhesive compositions were then subjected to various tests, the results of which are reported in Tables 2-6.
[0088] [Table 1a]
[0089] [Table 1b]
[0090] Testing Method <Shear strength> The shear strength of the anti-flutter adhesive composition was measured according to SAE J1523. The substrates were prepared by wiping with acetone and air drying for 5 minutes. The anti-flutter adhesive composition was extruded onto the surface of the substrate to form an overlapping adhesive area of 25 x 25 mm, an adhesive thickness of 3 mm, and the two substrates were mated. The anti-flutter adhesive composition was cured for 40 minutes at the desired temperature of 150-200 °C using an incubator BINDER M115. The shear strength values were measured using a Zwick Z010 at a pulling speed of 50 mm / min.
[0091] The result was passed if the shear strength value was 0.2Mpa or greater and the cured adhesive completely separated from one substrate surface (100% CF).
[0092] Even if the shear strength value was 0.2Mpa or more, if the cured adhesive broke and remained on the surfaces of both substrates after the two substrates were pulled apart, for example, 80% of the cured adhesive remained on one substrate and 20% of the cured adhesive remained on the other substrate (80% CF), the result was unacceptable.
[0093] <Appearance> 100 * 50 * 0.8mm (length * width * A cold rolled steel sheet having a size of 80 mm (thickness) was prepared. The anti-flutter adhesive composition was extruded onto the surface of the cold rolled steel sheet. * 10 * 6mm (length * width * The cold rolled steel was placed in a BINDER M115 incubator and the adhesive stripe was cured at the desired temperature of 150-200°C for 40 minutes. The cured adhesive stripe was cooled at room temperature for 24 hours.
[0094] The appearance of the cured adhesive stripe was checked using the finger press method by pressing the surface of the cured adhesive stripe with a finger. If the cured adhesive stripe was elastic, had a non-sticky surface, and was free of cracks, the result was reported as "OK." If the cured adhesive had any of the above defects, the result was reported as "Fail."
[0095] <Anti-sagging properties> The anti-sagging property of the anti-flutter adhesive composition was measured according to GB / T 31113-2014. * 50 * 0.8mm (length * width *A cold rolled steel sheet having a size of 22 mm (thickness) was prepared. The anti-flutter adhesive composition was extruded onto the surface of the cold rolled steel sheet to form a cylinder on the cold rolled steel sheet having a diameter of 22 mm and a height of 15 mm. The cold rolled steel sheet was then tilted at an angle of 70 degrees, and the cylindrical anti-flutter adhesive composition was left on the cold rolled steel sheet at 25° C. for 30 minutes. The displacement of the anti-flutter adhesive composition was recorded.
[0096] The tilted cold rolled steel, with the anti-flutter adhesive composition on the surface of the steel, was further cured at 155° C. for 30 minutes using an incubator BINDER M115. The displacement of the anti-flutter adhesive composition was also recorded.
[0097] If the displacement of the cylindrical anti-flutter adhesive composition was 5 mm or less at both 25° C. and 155° C., the anti-flutter adhesive composition passed the sagging prevention test.
[0098] [Table 2a]
[0099] [Table 2b]
[0100] [Table 3a]
[0101] [Table 3b]
[0102] [Table 4a]
[0103] [Table 4b]
[0104] [Table 5a]
[0105] [Table 5b]
[0106] The shear strength of the anti-flutter adhesive composition after curing on various substrates is reported in Tables 2-4, and the appearance of the cured anti-flutter adhesive composition is reported in Table 5. It was found that in order for the shear strength of the cured anti-flutter adhesive composition to be 0.2 Mpa or more, it is essential that the anti-flutter adhesive composition incorporates at least one PVC homopolymer having a K value of 67-75, at least one PVC copolymer having a K value of 60-75, at least one first organic peroxide having a decomposition temperature of 125-180°C, and at least one second organic peroxide having a decomposition temperature below 125°C. Moreover, the cured anti-flutter adhesive composition was completely separated from one substrate after the two substrates were pulled apart, and the cured anti-flutter adhesive composition had a good appearance. When the K value of the PVC polymer, the decomposition temperature of the organic peroxide, the amount of the PVC polymer, or the amount of the organic peroxide was not within the desired range, either the shear strength of the cured anti-flutter adhesive composition or the appearance of the cured anti-flutter adhesive composition deteriorated, as shown in Examples 5 to 8 and Examples 13 to 17.
[0107] [Table 6a]
[0108] [Table 6b]
[0109] The anti-sag properties of the anti-flutter adhesive composition are reported in Table 6. In order for the anti-flutter adhesive composition to have excellent anti-sag properties, the anti-flutter adhesive composition must contain at least one nano-sized inorganic filler and 150 to 250 μm of cellulose acetate. 2 It was found that it is essential to incorporate at least one fumed silica having a BET surface area of 1000 nm / g. If either the nano-sized inorganic filler or the fumed silica is missing from the composition, or the amount of the nano-sized inorganic filler or the fumed silica is not within the desired range, the cured anti-flutter adhesive composition has a large dislocation, as shown in Examples 21 and 22. Preferred aspects of the present specification include at least the following. [1] a) at least one ethylenically unsaturated rubber; b) at least one PVC homopolymer having a K value of 67 to 75; c) at least one PVC copolymer having a K value of 60 to 75; d) at least one epoxy resin; e) at least one epoxy hardener; f) at least one first organic peroxide having a decomposition temperature of 125 to 180° C.; and g) at least one second organic peroxide having a decomposition temperature of less than 125° C.; An anti-flutter adhesive composition comprising: The amount of the first organic peroxide is 0.4 to 0.8 wt. %, based on the total weight of the composition; and The anti-flutter adhesive composition, wherein the amount of the second organic peroxide is 0.2 to 1 wt %, based on the total weight of the composition. [2] The anti-flutter adhesive composition according to [1], wherein the PVC homopolymer preferably has a K value of 68 to 71. [3] The anti-flutter adhesive composition according to [1] or [2], wherein the amount of PVC homopolymer is preferably 6 to 15 wt. %, more preferably 7 to 10 wt. %, and even more preferably 8 to 9 wt. %, based on the total weight of the composition. [4] The anti-flutter adhesive composition according to any one of [1] to [3], wherein the PVC copolymer preferably has a K value of 63 to 70. [5] The anti-flutter adhesive composition according to any one of [1] to [4], wherein the amount of the PVC copolymer is preferably 2 to 5 wt %, more preferably 3 to 4 wt %, based on the total weight of the composition. [6] The anti-flutter adhesive composition according to any one of [1] to [5], wherein the first organic peroxide has a decomposition temperature of preferably 130 to 160°C, more preferably 130 to 140°C. [7] The anti-flutter adhesive composition according to any one of [1] to [6], wherein the first organic peroxide is preferably dicumyl peroxide. [8] The anti-flutter adhesive composition according to any one of [1] to [7], wherein the amount of the first organic peroxide is preferably 0.5 to 0.7 wt % based on the total weight of the composition. [9] The anti-flutter adhesive composition according to any one of [1] to [8], wherein the second organic peroxide has a decomposition temperature of preferably 50 to 120°C, more preferably 80 to 120°C, and even more preferably 100 to 115°C.
[10] The anti-flutter adhesive composition according to any one of [1] to [9], wherein the second organic peroxide is preferably 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane.
[11] The anti-flutter adhesive composition according to any one of [1] to
[10] , wherein the amount of the second organic peroxide is preferably 0.3 to 0.4 wt % based on the total weight of the composition.
[12] At least one nano-sized inorganic filler, and 150-250 m 2 / g, wherein the amount of said nano-sized inorganic filler is preferably 10-30 wt.%, more preferably 15-20 wt.%, based on the total weight of the composition, and 150-250 m 2 The anti-flutter adhesive composition according to any one of [1] to
[11] , wherein the amount of the fumed silica having a BET surface area of 1.5 to 3 wt. %, more preferably 2 to 3 wt. %, based on the total weight of the composition.
[13] The anti-flutter adhesive composition according to any one of [1] to
[12] , further comprising: (a) 2 to 10 weight percent of at least one ethylenically unsaturated rubber; (b) 6 to 15% by weight of at least one PVC homopolymer having a K value of 67 to 75; (c) 2-5 wt. % of at least one PVC copolymer having a K value of 60-75; (d) 1-6 wt. % of at least one epoxy resin; (e) 0.01-2 wt. % of at least one epoxy hardener; (f) 0.4-0.8 wt. % of at least one first organic peroxide having a decomposition temperature of 125-180° C.; (g) 0.2-1 wt. % of at least one second organic peroxide having a decomposition temperature less than 125° C.; (h) 0-30 wt. % of at least one nanosized inorganic filler; (i) 0 to 3% by weight, 150 to 250 m 2 at least one fumed silica having a BET surface area of 1.0 to 1.0 g / g; (j) 0-40 wt. % of at least one plasticizer; (k) 0-0.2 wt. % of at least one heat stabilizer; (l) 0-1 wt. % of at least one blowing agent; (m) 0-10 wt. % of at least one crosslinker; (n) 0 to 10% by weight of at least one additional inorganic filler different from the nanosized inorganic filler; and (o) 0-1 wt. % of at least one thermally expandable microsphere; Including, Here, the weight percent of all components totals 100 weight percent of the anti-flutter adhesive composition.
[14] A cured product of the anti-flutter adhesive composition according to any one of [1] to
[13] .
[15] An article bonded to or filled with the cured product of the sound deadening composition according to
[16] .
Claims
1. a) at least one ethylenically unsaturated rubber; b) at least one PVC homopolymer having a K value of 67 to 75; c) at least one PVC copolymer having a K value of 60 to 75; d) at least one epoxy resin; e) at least one epoxy hardener; f) at least one first organic peroxide having a decomposition temperature of 125 to 180° C.; and g) at least one second organic peroxide having a decomposition temperature less than 125° C.; An anti-flutter adhesive composition comprising: The decomposition temperature is a one-hour half-life temperature; The amount of the first organic peroxide is 0.4 to 0.8 wt. %, based on the total weight of the composition; and The anti-flutter adhesive composition, wherein the amount of the second organic peroxide is 0.2 to 1 weight percent based on the total weight of the composition.
2. The anti-flutter adhesive composition of claim 1 , wherein the PVC homopolymer has a K value of 68-71.
3. The anti-flutter adhesive composition according to claim 1 or 2, wherein the amount of PVC homopolymer is from 6 to 15% by weight, based on the total weight of the composition.
4. The anti-flutter adhesive composition of any of claims 1 to 3, wherein the PVC copolymer has a K value of 63-70.
5. The anti-flutter adhesive composition according to any of claims 1 to 4, wherein the amount of PVC copolymer is from 2 to 5 wt%, based on the total weight of the composition.
6. The anti-flutter adhesive composition according to any one of claims 1 to 5, wherein the first organic peroxide has a decomposition temperature of 130 to 160°C.
7. The anti-flutter adhesive composition of any one of claims 1 to 6, wherein the first organic peroxide is dicumyl peroxide.
8. The anti-flutter adhesive composition of any one of claims 1 to 7, wherein the amount of the first organic peroxide is 0.5 to 0.7 wt %, based on the total weight of the composition.
9. The anti-flutter adhesive composition according to any one of claims 1 to 8, wherein the second organic peroxide has a decomposition temperature of 50 to 120°C.
10. The anti-flutter adhesive composition of any one of claims 1 to 9, wherein the second organic peroxide is 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane.
11. The anti-flutter adhesive composition according to any one of claims 1 to 10, wherein the amount of the second organic peroxide is from 0.3 to 0.4 wt%, based on the total weight of the composition.
12. At least one nano-sized inorganic filler, and 150 to 250 m 2 / g, wherein the amount of said nano-sized inorganic filler is 10 to 30 wt. %, based on the total weight of the composition, and 2 The anti-flutter adhesive composition according to any one of claims 1 to 11, wherein the amount of said fumed silica having a B.E.T surface area of 1.5 to 3 wt. %, based on the total weight of the composition.
13. The anti-flutter adhesive composition according to any one of claims 1 to 12, comprising: (a) 2 to 10 weight percent of at least one ethylenically unsaturated rubber; (b) 6 to 15% by weight of at least one PVC homopolymer having a K value of 67 to 75; (c) 2-5 wt. % of at least one PVC copolymer having a K value of 60-75; (d) 1 to 6 weight percent of at least one epoxy resin; (e) 0.01 to 2 wt. % of at least one epoxy hardener; (f) 0.4 to 0.8 wt. % of at least one first organic peroxide having a decomposition temperature of 125 to 180° C.; (g) 0.2 to 1 wt. % of at least one second organic peroxide having a decomposition temperature less than 125° C.; (h) 0-30 wt. % of at least one nano-sized inorganic filler; (i) 0 to 3% by weight of 150 to 250 m 2 at least one fumed silica having a B.E.T surface area of 100 / g; (j) 0 to 40 wt. % of at least one plasticizer; (k) 0 to 0.2 wt. % of at least one heat stabilizer; (l) 0 to 1 wt. % of at least one blowing agent; (m) 0-10 wt. % of at least one crosslinker; (n) 0 to 10% by weight of at least one additional inorganic filler different from the nanosized inorganic filler; and (o) 0-1 wt. % of at least one thermally expandable microsphere; Including, Here, the weight percentages of all components total 100 weight percent of the anti-flutter adhesive composition.
14. A cured product of the anti-flutter adhesive composition according to any one of claims 1 to 13.
15. 15. An article adhered or filled with the cured anti-flutter adhesive composition of claim 14.
Citation Information
Patent Citations
Manufacturing method for car damping materials
CN102964649A
Anticorrosive sealant for hems in automobile manufacturing
CN104327783A
Shock-absorbing expansion adhesive for bonding zinc-magnesium-aluminum coated steel plate and preparation method thereof
CN110305610A
Damping adhesive for bonding with aluminum plate
CN110437767A
Adhesive composition
JP1992142382A